PENTINGNYA PERAN GURU DALAM PENINGKATAN KUALITAS PEMBELAJARAN PADA ANAK USIA DINI - Puji Hastuti, Dwi; Iswatiningsih, Daroe (Penerbit Lafadz Jaya, 2025)
The demand for qualified and professional teachers at this time is a must for all educators. In carrying out their duties, teachers are obliged to plan learning, carry out quality learning processes, to produce quality generations in the future. This study aims to describe the importance of professionalism, teacher competence in Early Childhood Education and the quality of PAUD teacher education in Musi Rawas Regency. The things explored in this study are the importance of the role of teachers in improving the quality of learning in early childhood. The research techniques used in this study were observation, document studies, and in-depth interviews. The data analysis used was descriptive analysis, namely an analysis that provides an overview of the things that have been studied. While the method used in this study was a qualitative analysis method. The analysis was carried out through several stages, namely: data collection, data reduction, data display, and conclusion drawing. Data validity, researchers used triangulation techniques, namely by using various methods to collect the same data from various data sources. Data were obtained from Educators of the Aisyiyah Bustanul Athfal Teachers Association, Musi Rawas Regency, South Sumatra Province. From the results of the study, it can be concluded that for IGABA educators in Musi Rawas Regency, by the end of 2024, there will be 8 new certified educators and 10 out of 71 educators who have passed the PPG Administration, almost half of the teacher data are still many high school graduates and there are still a lack of graduate educators who are linear with early childhood education. To get good quality in early childhood education, educators should have a Diploma four (D-IV) or Bachelor's degree (S1) in early childhood education, and other education relevant to the early childhood education system, or psychology obtained from an accredited study program, and have a PAUD Teacher Professional Education (PPG) certificate from an accredited university.